Fixing the future : how Canada's usually fractious governments worked together to rescue the Canada Pension Plan - Little, Bruce, 1945- (Rotman-UTP Publishing., 2008)
Bruce Little explains the CPP overhaul and shows why it stands as one of Canada's most significant public policy success stories, in part because it demanded an almost unparalleled degree of federal-provincial co-operation.